National Trends in Survival and Short-Term Outcomes of Periviable Births ≤24 Weeks Gestation in the United States, 2009 to 2018 - Doshi, Harshit; Shukla, Samarth; Patel, Shalinkumar; Cudjoe, Grace Annan; Boakye, Wendy; Parmar, Narendrasinh; Bhatt, Parth; Dapaah-Siakwan, Fredrick; Donda, Keyur (American Journal of Perinatology, 2022)
Objective Data from the academic medical centers in the United States showing improvements in survival of periviable infants born at 22 to 24 weeks GA may not be nationally representative since a substantial proportion of preterm infants are cared for in community hospital-based neonatal intensive care units. Our objective was to examine the national trends in survival and other short-term outcomes among preterm infants born at ≤24 weeks gestational age (GA) in the United States from 2009 to 2018.Study Design This was a retrospective, repeated cross-sectional analysis of the National Inpatient Sample for preterm infants ≤24 weeks GA. The primary outcome was the trends in survival to discharge. Secondary outcomes were the trends in the composite outcome of death or one or more major morbidity (bronchopulmonary dysplasia, necrotizing enterocolitis stage ≥2, periventricular leukomalacia, severe intraventricular hemorrhage, and severe retinopathy of prematurity). The Cochran–Armitage trend test was used for trend analysis. p-Value <0.05 was considered significant.Results Among 71,854 infants born at ≤24 weeks GA, 34,251 (47.6%) survived less than 1 day and were excluded. Almost 93% of those who survived <1 day were of ≤23 weeks GA. Among the 37,603 infants included in the study cohort, 48.1% were born at 24 weeks GA. Survival to discharge at GA ≤ 23 weeks increased from 29.6% in 2009 to 41.7% in 2018 (p < 0.001), while survival to discharge at GA 24 weeks increased from 58.3 to 65.9% (p < 0.001). There was a significant decline in the secondary outcomes among all the periviable infants who survived ≥1 day of life.Conclusion Survival to discharge among preterm infants ≤24 weeks GA significantly increased, while death or major morbidities significantly decreased from 2009 to 2018. The postdischarge survival, health care resource use, and long neurodevelopmental outcomes of these infants need further investigation.Key Points
Keywords: periviable preterm infants; survival; national inpatient sample; trends